VOLTAGE STABILIZERS AND THEIR TYPES - Abdurakhmanov , Bakhromjon; Temirova , Sugdiyona; Kholikova , Parizoda (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article analyzes the structure and operating principles of various voltage stabilizers. Their main advantages and disadvantages are presented. Furthermore, the fields of their application are provided depending on quality indicators.